2013
DOI: 10.1017/s0022215113001163
|View full text |Cite
|
Sign up to set email alerts
|

Nasolacrimal duct tumours in the era of endoscopic dacryocystorhinostomy: literature review

Abstract: Since the advent of endoscopic dacryocystorhinostomy, tumours are being diagnosed relatively early when smaller in size. Because of the rarity of this condition, it is advisable that such cases are managed through a dedicated epiphora service framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 69 publications
(46 reference statements)
1
15
0
1
Order By: Relevance
“…In the current study, the large majority of patients who underwent endoscopic DCR were found to have either inflamed or normal‐appearing sac mucosa, consistent with other reported findings of DCR surgery . The unsuspected neoplasms and granulomatous pathology rate in our series was 0.46% (n = 3), compared with 0% to 2.3% reported in the literature . The clinical experience of the senior surgeon in this study may account for this relatively low rate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the current study, the large majority of patients who underwent endoscopic DCR were found to have either inflamed or normal‐appearing sac mucosa, consistent with other reported findings of DCR surgery . The unsuspected neoplasms and granulomatous pathology rate in our series was 0.46% (n = 3), compared with 0% to 2.3% reported in the literature . The clinical experience of the senior surgeon in this study may account for this relatively low rate.…”
Section: Discussionsupporting
confidence: 90%
“…2,3,6,7,[13][14][15] The unsuspected neoplasms and granulomatous pathology rate in our series was 0.46% (n = 3), compared with 0% to 2.3% reported in the literature. [2][3][4][5][6][7][8][9][10][11][14][15][16][17][18] The clinical experience of the senior surgeon in this study may account for this relatively low rate. In all three unanticipated cases, the patient history, endoscopic examination, CT imaging, and intraoperative findings were not suggestive of neoplastic or granulomatous inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…determined a rate of proliferative diseases of 2.53% (12 tumours) in 474 patients at the Department of Ophthalmology at the Friedrich‐Alexander‐University in Erlangen, Germany. Tanweer et al . postulated a rate of 0.76% (4 neoplasms) in 525 patients .…”
Section: Discussionmentioning
confidence: 99%
“…1 The conditions causing nasolacrimal duct obstruction (NLDO) have an estimated incidence of 66% of all distal acquired forms, 1 and can be caused by different factors such as tumours, auto-immune diseases, systemic therapy (5-fluorouracil administration and iodine-131) and, in the absence of other factors, the stenosis is usually described as primary acquired nasolacrimal duct obstruction (PANDO). [1][2][3][4][5][6][7][8][9][10][11] In the literature different procedures have been described, both surgical and non-surgical, which can be used to treat distal acquired obstruction with a range of success rates. In a recent review, it was pointed out, based on the functional success rates, that external dacryocystorhinostomy (EXT-DCR) and endoscopic endonasal dacryocystorhinostomy (END-DCR) can be considered as the treatments of choice.…”
Section: Introductionmentioning
confidence: 99%